Quantitative trait loci for mature embryo culturability traits from Yuanjiang common wild rice (Oryza rufipogon Griff.) - Zhang, Kun; Yin, Zheng; Xu, Xu; Pu, Chao; Li, Qi; Wu, Di; Sun, Chuanqing; Fu, Yongcai (The Indian Journal of Genetics and Plant Breeding, 2016)
Low callus subculture and regeneration ability are the main factors restricting the genetic transformation potential of indica rice varieties. In the present study, an Oryza rufipogon introgression line population in the background of indica cultivar 93-11 was used to evaluate mature embryo culturability after callus induction, two-round of subculture, and differentiation of culture. A total of 25 quantitative trait loci related to tissue culturability were detected that included QTLs for callus browning index after one- and two-round subculture and callus regeneration rate. Among them, QTLs detected at the RM335 locus on chromosome 4 were found to control callus browning index after one- and two-round subculture and accounted for 11 and 15 % of the phenotypic variation. QTLs detected at the RM341 locus on chromosome 2 and at the RM8206 on chromosome 9 were found to control regeneration rate with 10 % contributions to the observed variation, respectively. The alleles of O. rufipogon were found to reduce callus browning and were possibly involved in the improvement of callus differentiation ability. Six introgression lines with excellent culturability characteristics were identified. It is expected that these lines will be useful materials for genetic transformation and fine mapping of culturability-trait.